Parâmetros genéticos e fenotípicos para resistência aos nematoides das galhas e características comerciais em alface - Costa, Aline de Paula (2023)
The continuous rise in temperature, caused by climate change, contributes to the occurrence of early flowering and the incidence of pathogens, such as root-knot nematodes, in lettuce, even with advances obtained through genetic improvement programs. The use of resistant cultivars associated with biological control as a method of controlling the root-knot nematode (Meloidogyne spp.) is efficient and safe, as it reduces the pathogen population in the soil, without the use of chemical products or even cultural practices that burden production. Associated with this, plants tolerant to early flowering generate plants with leaves of ideal size and weight. Knowing the genetic aspects involved in the important traits, which are sought in a breeding program, are of great importance to establish adequate methods and guarantee greater success of the program. The objective of this work was to estimate genetic and phenotypic parameters for traits of importance in lettuce breeding for tropical conditions. The cultivars Regina 71 (smooth type, susceptible to root-knot nematodes and tolerant to early flowering) and Grand Rapids (curly type, resistant to root-knot nematodes and susceptible to early flowering) were used as parents. Plants from both parents and from the F1 and F2 generations, originating from the cross, were evaluated for characteristics of resistance to the root-knot nematode, based on a grade criterion for the incidence of galls on the roots (ING); edge type (TBF) and leaf blade (TLF) and tolerance to early flowering, considering the number of days to start flowering (NDF). Once the results were obtained, the following genetic and phenotypic parameters were estimated for each of the evaluated traits: heritability in the broad sense, measure of additive and dominance effects, average degree of dominance and gains by selection. It was concluded that there is genetic variability for all traits. There is also a prevalence of additive effects for all traits, with the occurrence of low dominance; The TBF and TLF traits showed high heritability in the broad sense, (74%) and (77%), respectively; for the characteristics of ING and NDF, the values were lower, (43%) and (41%), respectively. For the NDF characteristic, the occurrence of transgressive segregation was also verified. The predominance of additive effects, associated with heritability values in the broad sense from median to high, and also the occurrence of transgressive segregation for the NDF trait, indicates the possibility of success in the selection of new heat-tolerant lettuce genotypes with resistance to Meloidogyne spp.